Identificación de las zonas susceptibles a inundaciones en la cabecera cantonal, del cantón las Naves, periodo diciembre 2021 – mayo 2022. - Meza Armijos, Marlon Jhonathan (2022)
The present investigative work has the purpose of identifying the areas susceptible to floods, through the free access Software International River Interface Cooperative "International River Interface Cooperative" (IRIC) and the Geographic Information System (GIS) in the cantonal head of the Las Naves canton. Currently, the "Naves Chico" and "Suquibí" rivers have become a danger to the population due to the constant flooding that has occurred in Las Naves and also, because there is no efficient drainage and protection system against floods. , which has caused physical, economic and environmental damage in the cantonal capital and has represented a threat to the study population, which is 350 families. The research is exploratory, descriptive and also field type. The research design is non- experimental, cross-sectional, and the methodology used has a mixed qualitative- quantitative approach, in addition, it was carried out in four phases; Preliminary Phase, Exploratory Phase, Execution Phase and Results Phase. The population sample came from 175 families. The techniques applied were through the Qgis program to create the basin for the study, the HEC-HMS program to establish the design hyetogram to know the behavior of the river and the design hydrograph to know the flow of water during an extreme event. , and the free software IRIC to carry out the flood model of the Naves Chico canton, the statistical software SPSS version 24 in Spanish was also used for data processing, in which a probabilistic sampling was applied to the study population, from an interview Semi-structured, the ArcMap program to determine the location of the houses in the area of influence to floods in the cantonal capital. From the results obtained, a hydrological model was made using the hydrological data processing systems (HEC-HMS) and a Hydraulic modeling (IRIC), which shows that there could be floods of up to almost 3 meters in the height of the water and the elaboration from the map of the area most susceptible to flooding, a diagnosis was also made on the risks of flooding according to the perspective of the population, most agree that the river represents a threat, that response agencies should pay more attention to these events and every year the river leaves economic losses in the houses located on the banks xix of the Naves Chico river, finally, adaptation measures and mitigation strategies focused on structural, non-structural and environmental measures. Keywords: Floods, Susceptible Zones, Hydrological Modeling, Hydraulic Modeling, Hazard, Geographic Information Systems, Mitigation Strategies, Adaptation Masures.